Pengaruh Kemampuan Teknik Personal, Keterlibatan Pemakai, Pelatihan Dan Pendidikan Pada Kinerja Sistem Informasi Akuntansi - Putu Ardiwinata, I Gusti Ngurah; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p09, 2019)
Information systems are the basis for the running of business today. Organizations need information systems to maintain competitiveness. The purpose of this study was to find out and obtain empirical evidence regarding the influence of personal technical skills, user involvement, training and education on the performance of accounting information systems. The population of this research is all LPD employees in the city of Denpasar. The sampling technique used was purposive sampling, so that the number of respondents obtained as many as 99 employees. Respondents in this study were the chairman, administration, cashier / admin and employees in the LPD who had used computer-based SIA directly. The analysis technique used is multiple linear regression analysis. The results of this study indicate that personal technical abilities, user involvement, and training and education have a positive and significant effect on the performance of accounting information systems in LPD in Denpasar City. Keywords : Personal technical skills, user involvement, training and education, SIA performance